Evaluasi Manajemen Reproduksi Ternak Sapi Potong di Desa Bajang Kecamatan Talun Kabupaten Blitar Jawa Timur - Anggy Anggara Putra Setna; Enike Dwi Kusumawati; Tri Ida Wahyu Kustyorini (Jurnal Ilmu dan Industri Peternakan, 2025)
The purpose of this study was to determine the evaluation of reproductive management in beef cattle in Talun District, Blitar Regency, East Java. This research activity was carried out in Desember 2024 in Bajang Village, Talun District, Blitar Regency, East Java. The research material was all beef cattle farmers in Bajang Village, Talun District, Blitar Regency, East Java. The research method used was a case study using information gathering tools, namely observation, interviews, questionnaires and documentation. The variables in this study include various things such as age of first mating, puberty, Estrus Cycle, Post Partum Estrus, Post Partum Mating, Days Open, and Service Per Conception. Analysis of the results of the activity used descriptive analysis and compared with the literature. The results of the study showed that (1) The average age of first mating of female cattle in the research area was 19.3 months, (2) Puberty of female cattle occurred at an average age of 12.2 months, (3) The average estrus cycle lasted for 20.5 days, (4) Post Partum Estrus (PPE) occurred on average 69 days after parturition, (5) Post Partum Mating (PPM) was carried out on average 107 days after giving birth, (6) Days Open (empty period) lasted on average 5.2 months, (7) Service per Conception (S/C) on average was 1.97 times artificial insemination per pregnancy. The conclusion is that the reproductive management of beef cattle in Bajang Village, Talun District, Blitar Regency, showed quite good results, although there are still several challenges such as increasing the efficiency of artificial insemination and reducing the empty period more optimally.